A Review: Shed Light on Ayurvedic Description of Menopause (AYUSHDHARA, 2021)
Menarche and Menopause are the two important landmarks of reproductive life cycle of woman's life. Menopause is the most significant event that brings physical and mental transformation in the body. It is a natural phenomenon occurs at the age 45-55 years. This phase is associated with manifestation of aging process along with other symptoms such as irregular menstruation, hot flashes, vaginal dryness, urinary problems, changes in appearance, GIT related problems, mood swings, sleep disturbances, palpitations, changes in sexual desire, osteoporosis, heart disease. The group of signs and symptoms associated with the menopausal phase are termed as menopausal syndrome. In Ayurvedic classics, Menopause is the termed as ‘Rajonivrutti’ and menopausal syndrome as ‘Rajonivrutti anubandhaja vyadhies’. Acharyas described as it is normal physiological state. In Ayurveda, Menopausal symptoms are regarded as imbalance of the Tridosha, Dhatukshaya and disturbance in Agni which occurs naturally as consequence of aging process. Modern medicine treat this condition with Hormone Replacement Therapy (HRT) which results in various complications, but it is effective therapy for a short term use. Considering the limitations of treatment with modern medicine, Ayurveda provides excellent solution & effective medicament for transition period i.e. menopause. Ayurvedic treatment for menopause involves correcting hormonal imbalance with proper diet, lifestyle modification, Shamana, Shodhan chikitsa, Rasayan therapy.